Decoding the Code: The Use of Gen Alpha Slang in the University of Eastern Philippines - Ejercito, Wilson N. (Journal of Natural Language and Linguistics, 2025)
This research study was focused on the Gen Alpha Slangs in the University of Eastern Philippines. This research study aimed to collect slang expressions, categorize them according to the following categories: Shortenings/Abbreviation/Acronym, Neologism/Coinage, Meaning Re-assignment, Compounding, Wrong Talk Funny One, Flippant, Fresh and Creative, Interjection, and Imitative. This study determined the gloss or meaning of each slang expression collected from the student-participants according to its context. Further, this study employed “pagtatanong-tanong” in gathering the data through an informal interview. This study revealed that the students of the University of Eastern Philippines are certified users of the slang expressions. This study further revealed that the student-participants of this study are indeed users of different slang expression which can be categorized to different slang expressions. Furthermore, this study also found out that the slang expressions used by the student-participants has different gloss in reference to the context of each term.